2013
DOI: 10.1016/j.bodyim.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of pubic hair grooming among low-income Hispanic, Black, and White women

Abstract: The purpose of this paper was to describe pubic hair grooming behaviors (shaving, waxing, trimming or dyeing) and the extent to which grooming was related to demographic characteristics and sexual history among low-income Hispanic, Black, and White women. Data were collected from 1,677 women aged 16 to 40 years between July 2010 and August 2011 as part of a larger study. Participants completed a cross-sectional written survey. Multivariable analyses were used to identify correlates of pubic hair grooming. Bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
70
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 17 publications
(36 reference statements)
15
70
1
12
Order By: Relevance
“…Given the wide availability of explicit media depicting pubic hair grooming in women, it seems less likely that education is related to more exposure to popular culture ideals. Similar to other studies, 4,12 we found a difference in racial distribution of groomers, with white women being far more likely to groom than any other racial/ethnic group. This finding has been documented in a prior study 12 and seen as most likely to be related to cultural norms and ideals of beauty among different racial groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Given the wide availability of explicit media depicting pubic hair grooming in women, it seems less likely that education is related to more exposure to popular culture ideals. Similar to other studies, 4,12 we found a difference in racial distribution of groomers, with white women being far more likely to groom than any other racial/ethnic group. This finding has been documented in a prior study 12 and seen as most likely to be related to cultural norms and ideals of beauty among different racial groups.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies, 4,12 we found a difference in racial distribution of groomers, with white women being far more likely to groom than any other racial/ethnic group. This finding has been documented in a prior study 12 and seen as most likely to be related to cultural norms and ideals of beauty among different racial groups. Our study is unique in assessing the role of the partner in grooming.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with previously published rates of pubic hair removal, ranging from 48% to 87% for women and 33% to 50% for men, depending on age and sexual orientation. 2,3,5,12,14,20 Unlike prior studies that we are aware of examining trends in pubic hair removal, 6,12,20 this survey included respondents from a wide range of ages, geographic locations, and sexual activity patterns that mirrored the current population of the United States. 17 We found significantly greater prevalence of grooming among younger groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study only captured injuries warranting evaluation in an emergency department and thus likely underestimated the prevalence of all injuries related to grooming. Given the high prevalence of pubic hair grooming (50%-87%), 2,3,5,12 a better understanding of how grooming may lead to injury is warranted. We evaluated grooming behavior by using a survey distributed to a nationally representative sample of US men and women.…”
mentioning
confidence: 99%